Elastic and mechanical properties of Osmium Diboride under high pressure - Anas Shitu Anas; Tanveer Ahmad Wani Tanveer; Annabathini Geetha Bhavani Geetha; B. Prabhakar; Ravi Shanker Ahuja; Mohammad Aslam; Mohd Umair; Tara Prasad (Zaštita Materijala)
The approach towards designing superhard materials incorporates the lighter elements like Boron, Carbon and Nitrogen. With the application of developed DFT theoretical formalism, the calculation of the single crystal elastic constants for Osmium Diboride OsB2 under High Pressure from first principle calculations are described in this paper. The calculated mechanical properties using Voigt and Reuss approximation for Bulk (B), Young (E) and Shear Modulus (G) (in kbar) and Poisson ratio (n) for different pressure ranges (0to 200 GPa) have been reported.